Efektifitas Penggunaan Mobile Learning App Materi Fisika SMA Berbasis STEM sebagai Sumber Belajar Siswa Bahasa Indonesia terhadap Hasil Belajar - Apit Fathurohman; Ahmad Fali Oklilas; Leni Marlina; Lintang Auliya Kurdiati; Esti Susiloningsih; Azhar Azhar; Samsuryadi Samsuryadi (Postgraduate, University of Mataram, 2023)
This study aims to determine the effectiveness of using the STEM-Based Physics Mobile Learning App as a learning resource for students in Indonesia on learning outcomes. The method used in this research is the experimental method. To describe the experimental results, statistical analysis techniques were used, namely the N-Gain technique. The research was conducted at SMAN 1, Air Sugihan, Ogan Komering Ilir Regency. The analysis of the data reveals that the improvement in learning outcomes in the experimental class compared to the control class is evidence of the usage of STEM-based high school physics learning applications as a learning resource for teachers and students. The experimental class's average post-test score was 81.1, while the control class' average post-test score was 72.22